Commemorative insights: the best of life, in death. Issue 4 (4th July 2021) - MacCarthy, Martin; Heng Rigney, Ker Ni
ABSTRACT: This study explores visitor experience at the National Anzac Centre in Western Australia using multiple qualitative methods. Initially, Nethnography is used to assemble a blend of lived experience and online non-dialogical commentary. Nethnography (an alternative to Netnography) is used here as a mechanism for data grooming. Three data sets inform this study: 500 Trip Advisor comments, 500 Visitors' Book comments and four days of participant observation. The data are then analysed using Reflexive Thematic Analysis and Leximancer in the unsupervised mode. This methodological collage is designed to improve the veracity of interpretation through both lived experience and triangulation across data sources. Findings suggest a significant visitor-thirst for the positive aspects of commemoration. By the same token no respondent reported being motivated by schadenfreude, mortality salience or death. If a certain fascination with, and commodification of death defines popular dark tourism then commemorative tourism's relegation of death indicates exception. It would seem commemorists relegate death and darkness to mere context, while gravitas, ritual and cultural validation transcend the superficial and the kitsch. Meanwhile, visitors to the National Anzac Centre concentrate on more endearing traits including sacrifice, love, loss and the nobility of caritas.